EVOLUTION OF THE COURT / TRIBUNAL CONCEPT: Should it go in the Direction of its Europeanization? - Matić Matešković, Ines; Bodul, Dejan; Bartulović, Željko (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
We live in a time of rapid social, economic and legal changes. Traditional legal concepts, such as court/tribunal are evolving. Modernization of law harmonizes it with needs of the time in which is applied. Organizational and functional modernization of courts should be oriented towards Europeanization. This must be understood as a broader process than the mere reception of European law and taking over legal institutes from other legal systems without analyse of what they mean in them and without analysing whether they are in line with legal tradition and/or how to include them in domestic legal system. Authors analyse historical aspects of court system, how and whether to reform the courts in functional and organizational terms, which organizational structures in that case to entrust with the exercise of judicial power and whether it is possible to maintain the principles based on classical legal standards.